Functions and emerging applications of bacteriocins. (February 2018) - Chikindas, Michael L; Weeks, Richard; Drider, Djamel; Chistyakov, Vladimir A; Dicks, Leon MT
Graphical abstract: Highlights: Bacteriocins play an integral, multifaceted role in microbial ecology. Targeted and controlled delivery should improve the efficacy of bacteriocins. Bacteriocins' diverse functions inspire their multidimensional applications. Abstract : Bacteriocins, defined as ribosomally synthesized antimicrobial peptides, have traditionally been used as food preservatives, either added or produced by starter cultures during fermentation. In-depth studies of a select few bacteriocins opened exiting new research fields and broadened the application of these antimicrobial peptides. The possibility of developing bacteriocins into next generation antibiotics, accompanied with the rapid development in genetics and nanotechnology, paves the way to even more fascinating applications such as novel carrier molecules (delivery systems) and the treatment of cancer. Also, some bacteriocins are found to regulate quorum sensing which suggests novel applications for this group of substances. While there is some interesting translational research on bacteriocins from Gram-negative bacteria, the majority of application-oriented studies are focused on bacteriocins from Gram-positive microorganisms, mostly lactic acid bacteria. The applications of bacteriocins are expanding from food to human health.